2016
DOI: 10.1016/j.schres.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Change in newspaper coverage of schizophrenia in Japan over 20-year period

Abstract: a b s t r a c t a r t i c l e i n f oIn Japan, schizophrenia was renamed in 2002 to reduce the stigma that people with schizophrenia are dangerous. However there has been little research on the potential anti-stigma effect of renaming. The present study aimed to examine whether portrayals of schizophrenia in newspapers as dangerous have been varied across renaming of the disease. To achieve this goal, newspaper articles containing the previous and new Japanese names for schizophrenia, published in the decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Countries were chosen for the reasons stated in the introduction section after the first search, when articles covering newspapers in different countries were subjected to a preliminary screening. Only articles referring to mental health in general were chosen, with the exception of Aoki et al (2016) which focus specifically on schizophrenia. This article was chosen due to the significant relevance the change in the Japanese word for Schizophrenia could have had on reducing the stigma.…”
Section: Design/methodology/approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries were chosen for the reasons stated in the introduction section after the first search, when articles covering newspapers in different countries were subjected to a preliminary screening. Only articles referring to mental health in general were chosen, with the exception of Aoki et al (2016) which focus specifically on schizophrenia. This article was chosen due to the significant relevance the change in the Japanese word for Schizophrenia could have had on reducing the stigma.…”
Section: Design/methodology/approachmentioning
confidence: 99%
“…Positively, there was also a significant rise in the proportion of articles about the awareness and understanding of mental health concerns during this period. A more specific study concerning only media coverage of schizophrenia from 1992 to 2012 showed that there was a decrease in the ratio of articles about schizophrenia and danger related to that of bipolar disorder (Aoki et al, 2016). This decrease coincides with the renaming of the term schizophrenia for a less stigmatising term in some Asian countries (e.g., Japan, Honk Kong, Taiwan, South Korea) in the early 2000s.…”
Section: Japanmentioning
confidence: 99%
“…Among different national media, newspapers have a special role because they can be considered an index of wider public opinion (Aoki et al, 2016) and a privileged source of information on mental health (Whitley and Wang, 2016). In a recent retrospective analysis (2016), Aoki and colleagues showed that 14-49% of articles on mental disorders published in newspapers highlight the association between mental disorders and dangerousness.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is the most frequent mental disorder reported in newspapers (Aoki et al, 2016;Carpiniello et al, 2007;Goulden et al, 2011;Nawková et al, 2012Nawková et al, , 2012 and it still represents the most stigmatized disorder for patients and their family members (Corrigan and Watson, 2002). Therefore, the need to challenge stigma associated with schizophrenia has become an ethical and public health priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation